Implementasi Talent Management System dalam Mengembangkan High Potensial Employee : Studi Succession Planning PT. Surya Pratista Hutama (Lembaga Pengembangan Kinerja Dosen, 2025)
Increasing competition in the food industry requires companies to not only focus on product innovation and market expansion but also on strengthening internal human resource capabilities through long-term strategies. PT. Surya Pratista Hutama addresses this challenge by implementing a Talent Management Sistem (TMS) designed to identify, develop, and retain high-potential employees (HiPos), while simultaneously ensuring sustainable leadership development and succession planning. This study employed a qualitative case study approach by utilizing observations, in-depth interviews, and a paper review to obtain comprehensive insights into the company’s practices. The findings reveal that the identification of HiPos is carried out through a rigorous and consistent process using the 9-box grid as a key assessment tool. The emphasis on consistency in evaluation highlights the organization’s effort to ensure fairness and accuracy. Employee development is facilitated through multiple strategies, including formal training, mentoring programs, job rotation, and other structured learning initiatives. Retention strategies focus on providing competitive compensation packages, developing financial literacy skills, and fostering a collaborative organizational culture that values employee contributions. The implementation of TMS at PT. Surya Pratista Hutama has shown positive impacts, particularly in reducing employee turnover rates and improving leadership performance. However, the study also identifies several challenges, especially related to the need for clearer procedural guidelines and more specific development strategies to optimize outcomes. Overall, this research demonstrates that a well-structured TMS can serve as an effective mechanism for building sustainable human resource capabilities in highly competitive industries such as food manufacturing.